1974
DOI: 10.1111/j.1469-8137.1974.tb01312.x
|View full text |Cite
|
Sign up to set email alerts
|

ON HORMONES AND WEEPING: ASYMMETRIC HORMONE DISTRIBUTION AND THE PENDULOUS GROWTH HABIT OF THE WEEPING MULBERRY, MORUS ALBA VAR. PENDULA

Abstract: SUMMARYThe possibility that asymmetric hormone distribution causes downward bending of weeping mulberry {Morus alba var. pendula) twigs was investigated. By extraction, bioassay and gas chromatography it was shown that while upper and lower twig sections had no differences in auxin activity, the two sides differed considerably in content of GA and ABA. The lower side contained high levels of endogenous GA while the upper side had higher concentrations of ABA. The significance of these results and their possibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Pillar peach trees (tac1 mutants) were found to have elevated auxin concentrations in their shoot tips relative to standard cultivars 36 . Further, altered Abscisic Acid (ABA) localization in branches was associated with a weeping mulberry tree architecture, and tac1 is epistatic to a weeping peach architecture 32,37 . To investigate if TAC1-or LAZY-mediated shoot orientations are associated with hormone concentrations, LC/MS/MS was performed on extracts from Arabidopsis tac1, lazy1, and Col shoot tips, stems (just below the tip), and branch tips from plants ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Pillar peach trees (tac1 mutants) were found to have elevated auxin concentrations in their shoot tips relative to standard cultivars 36 . Further, altered Abscisic Acid (ABA) localization in branches was associated with a weeping mulberry tree architecture, and tac1 is epistatic to a weeping peach architecture 32,37 . To investigate if TAC1-or LAZY-mediated shoot orientations are associated with hormone concentrations, LC/MS/MS was performed on extracts from Arabidopsis tac1, lazy1, and Col shoot tips, stems (just below the tip), and branch tips from plants ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, GA application was reported to rescue weeping peach and cherry phenotypes via increased tension wood (24)(25)(26). Reches et al (28) found that the lower half of actively growing weeping mulberry (Morus alba Var. pendula) tree branches had significantly greater GA levels than the upper side.…”
Section: Discussionmentioning
confidence: 99%
“…To date, no causative alleles for weeping tree traits have been reported. Aberrant GA hormone concentrations and localization have been reported for a few weeping tree phenotypes, but the underlying significance of the observed differences remains unknown (24)(25)(26)(27)(28).…”
Section: Significancementioning
confidence: 99%
“…Plant architecture is controlled by auxin and gibberellin 3 , 4 , 6 , 26 . Auxin plays key roles in regulating meristem development and secondary growth processes.…”
Section: Discussionmentioning
confidence: 99%
“…Pendulous-stem (weeping) plants have high ornamental value during the leaf expansion period and after defoliation because of their naturally weeping stems and peculiar shape. Plants with the pendulous-branched (weeping) trait are observed in the herbaceous plant Arabidopsis 2 and many woody species, such as willow ( Salix matsudana ) 3 , Prunus persica 4 , and Morus alba 5 , 6 . However, the phenotype of weeping traits is complicated.…”
Section: Introductionmentioning
confidence: 99%